Detecting Rice Growth Using ALOS Multispectral and Synthetic Aperture Radar - Bambang Hendro Trisasongko; Dyah Retno Panuju; La Ode Syamsul Iman (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Rice monitoring is a substantial to Asian countries, including Indonesia, since most inhabitants consume rice on a daily basis. As field survey requires substantial time and budget, one relies on remotely sensed data, especially taken through spaceborne platform. This research discusses multispectral and linearly polarized Synthetic Aperture Radar (SAR) from Advanced Land Observing Satellite and their applications to observe various rice growth information. It appears that both sensors provided useful rice growth data leading to the possibility on improving rice field information extraction. Classification scheme by means of Random Forest suggested that both data were fairly acceptable for timely monitoring.